The Effect of Organic Fertilizers on Growth and Yield of Water Spinach (Ipomoea reptans Poir) - Selvia Dewi Pohan (Department of Crop Science, Faculty of Agriculture, Andalas University, 2021)
Water spinach (Ipomoea reptans Poir) had been identified as a nutritious vegetable with high demand in Indonesia. Besides, this plant also has been evidenced to play an important role in environmental cleaning as phytoremediator. The study about the effect of organic fertilizers on the growth and yield of water spinach (Ipomoea reptans Poir) has been conducted in the Green House of Biology Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Medan. The study aims to investigate the most effective type of fertilizers and the dose for water spinach’s (Ipomoea reptans Poir) growth and yield. A Completely Randomized Factorial Design was designed for the experiment with two factors and three repetitions. The first factor is the type of fertilizer (chicken manure, cow manure, and compost), and the second factor is the dose of the fertilizer (1:1, 2:1, and 3:1). The parameters such as plant height, number of shoots, number of leaves, fresh weight, dry weight, leaf’s total chlorophyll content, and water content were measured to evaluate plant growth and yield. The General Linear Model used SPSS 21 programs was applied to analyze the collected data. Study results revealed that cow manure increased plant growth and yield significantly with dose 2:1 as the finest treatment, followed by dose 3:1. Cow manure also increased total chlorophyll content (8.0574c mg. L-1), with the most suitable dose was 2:1 (8.2807 mg. L-1). The plant’s water content tended to be high in chicken manure (93%), and the lower water content was in cow manure with dose 3:1 (87.5%).